Case Report: Rapid resolution of fever after initiation of third-line rescue treatment with upadacitinib for acute severe ulcerative colitis in two young men - Pinzaru, Dan; Kreysing, Martin; Lesmeister, Tony; Schwandner, Miriam; Michl, Patrick; Gauss, Annika (Frontiers in Gastroenterology, 2025)
IntroductionAcute severe ulcerative colitis (ASUC) is a life-threatening condition in patients with ulcerative colitis with overwhelming systemic inflammation. In case of steroid-refractory courses, the mainstay of therapy is currently infliximab or a calcineurin inhibitor, weighed against colectomy. Recently, Janus kinase (JAK) inhibitors have been shown to result in rapid and persistent responses even in steroid-refractory patients, so that their position in the therapeutic algorithm of ASUC has to be determined. We present—to our best knowledge, for the first time—two cases in which upadacitinib was administered as a third-line rescue therapy in steroid- and infliximab-refractory patients with persistent fever.Case presentationsA 33- and a 28-year-old man, both newly diagnosed with ulcerative pancolitis, presented with steroid-refractory courses of ASUC. Both suffered from fever with temperatures of >39°C in spite of empirical antibiotic therapy, and infection was carefully excluded. In both, infliximab at 5 mg/kg body weight failed to resolve the fever, and second salvage therapy with upadacitinib 45 mg led to swift resolution of the fever and to overall clinical response. Both patients were under ongoing upadacitinib treatment, and in outpatient surveillance, one of them in steroid-free clinical remission up to his last follow-up one year post treatment initiation, the other one up to his last follow-up four months post treatment initiation.ConclusionUpadacitinib seems to be a valuable option even as a second salvage therapy in ASUC. Randomized controlled trials are warranted. However, it has to be kept in mind that ASUC, especially with septic symptoms such as fever, remains a life-threatening condition in which surgery always has to be evaluated, and that multiple overlapping immunosuppressive therapies may cause severe complications, such as infections.